Being visible in public space: The normalisation of asymmetrical visibility. (March 2017) - Hatuka, Tali; Toch, Eran
Over recent decades, cities have been radically transformed by information and communication technologies (ICTs) that modify people's daily lives by reorganising mobility, infrastructure systems and physical spaces. However, in addition to the role that technology plays in the development of the infrastructure in our cities, it is also being used 'as a means of control'. This view of technology as a disciplinary tool that restructures space, time and the relations among activities has been promoted by scholars who have shown that technology is also a means of saturating and sustaining contemporary capitalist societies and deepening inequalities. However, the situation is far more complex than that. Technology is not only used top-down but also bottom-up, with individuals using technological devices to share and enhance their visibility in space. This bidirectional paradigm – of vertical surveillance and horizontal sharing – contributes to a sense of 'being exposed' in public space that normalises practices of sharing personal data by individuals and thus results in diminished privacy. This argument is supported by an experiment conducted on smartphone users that includes personal interviews and the use of a smartphone Android application that combines online tracking with experience sampling. The findings show a convergence between the online and offline worlds (a 'public' situation in the offline world is also considered as such in the online world), which is a condition that contributes to the normalisation of 'asymmetrical visibility'. Based on these results, the paper ends with a discussion of the contemporary meaning of public space.